Hematological And Bacteriological Indicators Of Comparative Assessment Of Methods Of Closing A Median Laparotomy Incision In A Pet - Yertleuova, B. O.; Ichshanova, A. S.; Gabdullin, D. Y.; Sidikhov, B. M.; Valiyeva, Zh. M.; Marat, M. B. (Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-1 (75). Ч. І. - Р. 230-239, 2024)
The article presents the results of a comparative study in the selection of suture types and materials that provide effective and periodic healing in order to avoid complications after closing laparotomy incisions along the white line during operations on the abdominal area of pets (dogs, cats) and to create conditions for the formation of a complete healing level of sutures in the operated area before sending them back to the habitat. In the postoperative period, in the conditions of a veterinary clinic, additional hemotological and bacteriological studies were carried out during the healing of the incision in the period corresponding to the time of maintenance. Blood hematolgic indicators on the day of the operation, the initial state of the blood was determined. The dynamics of hematological changes was observed on the 3rd, 5th, 7th days of the postoperative period, the bacteriological condition was determined during the operation and on the 7th day of control. Hematological blood indicators obtained according to the results of the study showed the level of regenerative displacement in dogs and cats of all experimental groups. Due to the relatively selected suture type in terms of bacteriological condition, it was shown that the level of microbial contamination was also much lower compared to other research groups, since the closure of the wound surface in dogs and cats in the first experimental group was formed in a short time.
Keywords: журнал кокснво; ветеринария; ovariohysterectomy; dog; cat; laporotamia; microbial contamination; лапаротомные разрезы; ветеринарная хирургия